C1q Nephropathy: The Unique Underrecognized Pathological Entity. (10th November 2015) - Devasahayam, Joe; Erode-Singaravelu, Gowrishankar; Bhat, Zeenat; Oliver, Tony; Chandran, Arul; Zeng, Xu; Dakshinesh, Paramesh; Pillai, Unni
Abstract : C1q nephropathy is a rare glomerular disease with characteristic mesangial C1q deposition noted on immunofluorescence microscopy. It is histologically defined and poorly understood. Light microscopic features are heterogeneous and comprise minimal change disease (MCD), focal segmental glomerulosclerosis (FSGS), and proliferative glomerulonephritis. Clinical presentation is also diverse, and ranges from asymptomatic hematuria or proteinuria to frank nephritic or nephrotic syndrome in both children and adults. Hypertension and renal insufficiency at the time of diagnosis are common findings. Optimal treatment is not clear and is usually guided by the underlying light microscopic lesion. Corticosteroids are the mainstay of treatment, with immunosuppressive agents reserved for steroid resistant cases. The presence of nephrotic syndrome and FSGS appear to predict adverse outcomes as opposed to favorable outcomes in those with MCD. Further research is needed to establish C1q nephropathy as a universally recognized distinct clinical entity. In this paper, we discuss the current understanding of pathogenesis, histopathology, clinical features, therapeutic options, and outcomes of C1q nephropathy.